Brake-by-Wire Comes To Freight Trains. - Maryott, D. (IEEE spectrum)
This article deals with the electronically controlled pneumatic brakes that could help stop accidents and speed cargo. Electronically controlled pneumatic brakes (ECP) are intended to displace the venerable air brake system first patented by George Westinghouse in 1869 and now used around the world. New rules by the Federal Railroad Administration (FRA) may finally start to make ECP mainstream in the United States, which is home to the largest rail freight network in the world.